Non-Verbal Codes in The Activity of Mabebasan Art - Sudewi, Putu Wahyu; Dollah, Syarifuddin (ELT Worldwide: Journal of English Language Teaching, 2025)
This research explores the role of non-verbal communication in mabebasan performances, a traditional Balinese art. A qualitative approach was adopted to examine the non-verbal codes, particularly kinesics such as hand movements, body postures, and head gestures, and their cultural significance in enhancing the emotional expression and clarity of the narrative. Data was collected from 2 participants, including pangawacen (chants) and paneges/pangartos (translators), using semi-structured interviews and observation. The study found that hand gestures, body movements, and head gestures played crucial roles in expressing emotion, ensuring synchronization between performers, and conveying the narrative’s moral and emotional depth. Hand gestures helped to highlight key moments and connect with the audience, while body movements and head gestures facilitated role transitions and emphasized significant themes.